Compound Identification Using Liquid Chromatography and High-Resolution Noncontact Fraction Collection with a Solenoid Valve. (December 2019) - Jonker, Willem; de Vries, Koen; Althuisius, Niels; van Iperen, Dick; Janssen, Elwin; ten Broek, Rob; Houtman, Corine; Zwart, Nick; Hamers, Timo; Lamoree, Marja H.; Ooms, Bert; Hidding, Johannes; et al.
We describe the development of a high-resolution, noncontact fraction collector for liquid chromatography (LC) separations, allowing high-resolution fractionation in high-density well plates. The device is based on a low-dead-volume solenoid valve operated at 1–30 Hz for accurate collection of fractions of equal volume. The solenoid valve was implemented in a modified autosampler resulting in the so-called FractioMate fractionator. The influence of the solenoid supply voltage on solvent release was determined and the effect of the frequency, flow rate, and mobile phase composition was studied. For this purpose, droplet release was visually assessed for a wide range of frequencies and flow rates, followed by quantitative evaluation of a selection of promising settings for highly accurate, repeatable, and stable fraction collection. The potential of the new fraction collector for LC-based bioactivity screening was demonstrated by fractionating the LC eluent of a mixture of estrogenic and androgenic compounds, and a surface water sample (blank and spiked with bioactives) combining mass spectrometric detection and two reporter gene assays for bioactivity detection of the fractions. Additionally, a mixture of two compounds was repeatedly LC separated and fractionated to assess the feasibility of the system for analyte isolation followed by nuclear magnetic resonance analysis.